2018
DOI: 10.1002/jcp.26357
|View full text |Cite
|
Sign up to set email alerts
|

Study on mechanism about long noncoding RNA MALAT1 affecting pancreatic cancer by regulating Hippo‐YAP signaling

Abstract: By investigating the migration and invasion ability in pancreatic cancer, this study probed into the lncRNA MALAT1 molecular mechanism on Hippo-YAP signaling. The expression of lncRNA MALAT1 in PC tissues and cells was detected by qRT-PCR and Western blot. The effect of si-MALAT1 on proliferation was determined by CCK-8 assay. Cell apoptosis, migration, and invasion were respectively detected by flow cytometry assay, wound healing assay, and transwell assay. Western blot and immunohistochemistry were successiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“…Many studies have revealed that YAP and TAZ were independent prognostic factors for PDAC patients and promoted PDAC initiation and progression [12,[40][41][42][43][44]. It also has been reported that Glucose Sensor O-GlcNAcylation, miR-181c, lncRNA MALAT1 and UCA1 promoted PDAC development, progression and chemoresistance via Hippo signaling [45][46][47][48]. The roles of YAP and TAZ have been widely studied, however, the expression, function and regulation of other core components of Hippo signaling, such as MOB1, still need further study.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that YAP and TAZ were independent prognostic factors for PDAC patients and promoted PDAC initiation and progression [12,[40][41][42][43][44]. It also has been reported that Glucose Sensor O-GlcNAcylation, miR-181c, lncRNA MALAT1 and UCA1 promoted PDAC development, progression and chemoresistance via Hippo signaling [45][46][47][48]. The roles of YAP and TAZ have been widely studied, however, the expression, function and regulation of other core components of Hippo signaling, such as MOB1, still need further study.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that these may participate in the mTOR signaling pathway, pathways in cancer, and the MAPK signaling pathway in PDAC. Diminished expression of MALAT1 decreases the expression of Yes-associated protein 1 (YAP1) and elevates large tumor suppressor 1 (LATS1) levels (27). It has been suggested that MALAT1 regulates PDAC via the Hippo-YAP pathway.…”
Section: Malat1mentioning
confidence: 99%
“…Pancreatic cancer (PC) ranks as the seventh leading cause of cancer-related death worldwide, accounting for approximately 4% of all cancer cases with about 330,000 deaths per year. 1 PC has also been highlighted as one of the most aggressive malignancies in digestive system, due largely to late diagnoses, high rate of mortality, as well as an increased potential of metastasis and malignancy. 2 Endothelial cells are a type of heterogeneous cell cluster located in the microvascular capillary beds of various organs, among which human microvascular endothelial cells (HMVECs) are unique yet unrecognizable in phenotype, function and structure.…”
Section: Introductionmentioning
confidence: 99%
“…G, The expression of hsa-miR-27a in GSE28955. miR-27a-3p, microRNA-27a-3p; BTG2, B-cell translocation gene 2; PC, pancreatic cancer; DEGs, differentially expressed genesSize of each list elements: specific(1) or shared by 2, 3, ... lists elements: specific(1) or shared by 2, 3, ... lists elements: specific(1) or shared by 2, 3, ... lists elements: specific(1) or shared by 2, 3, ... lists elements: specific(1) or shared by 2, 3, ... lists 4Number of elements: specific(1) or shared by 2, 3, ... lists 5 of VEGF, VEGFR, MMP-2 and MMP-9 following the treatment of miR-27a mimic, which was accompanied by a reduction after treatment with a miR-27a inhibitor (Figure 3G&H).Thus, miR-27a down-regulation was concluded to induce the inhibition of cell proliferation and invasion, and accelerated PC apoptosis.…”
mentioning
confidence: 99%